DFT Study with Inclusion of the Grimme Potential on Anatase TiO2: Structure, Electronic, and Vibrational Analyses - Albuquerque, Anderson R. [UNESP]; Garzim, Marcos L. [UNESP]; dos Santos, Ieda M. G.; Longo, Valeria [UNESP]; Longo, Elson [UNESP]; Sambrano, Julio R. [UNESP] (Amer Chemical Soc, 2012)
Periodic DFT/B3LYP calculations for TiO2 anatase bulk were carried out including semiempirical dispersive interactions (DFT-D2) to pure Khon-Sham DFT energy. From this standard methodology, van der Waals (vdW) radii were optimized to 1.4214 angstrom for titanium and 1.3420 angstrom for oxygen centers in order to achieve a better structural description. The results from this approach (here named DFT/B3LYP-D*) showed a better description for lattice constants, vibrational IR and Raman, energy band gaps, and bulk modulus than default DFT/B3LYP and DFT/B3LYP-D. The dispersion correction showed more reliable results and was necessary to achieve a good agreement with reported single crystal results, without new formalism or additional computational cost.